β-Cyclodextrin-Modified Laser-Induced Graphene Electrode for Detection of N6-Methyladenosine in RNA - Jingyi Guo; Mei Zhao; Xia Kuang; Zilin Chen; Fang Wang (Molecules)
Laser-induced graphene (LIG) possesses characteristics of easy handling, miniaturization, and unique electrical properties. We modified the surface of LIG by electropolymerizing β-cyclodextrin (β-CD), which was used to immobilize antibodies on the electrode surface for highly sensitive detection of targets. N6-methyladenosine (m6A) is the most prevalent reversible modification in mammalian messenger RNA and noncoding RNA, influencing the development of various cancers. Here, β-CD was electropolymerized to immobilize the anti-m6A antibody, which subsequently recognized the target m6A. This was integrated into the catalytic hydrogen peroxide–hydroquinone (H2O2-HQ) redox system using phos-tag-biotin to generate electrochemical signals from streptavidin-modified horseradish peroxidase (SA-HRP). Under optimal conditions, the biosensor exhibited a linear range from 0.1 to 100 nM with a minimum detection limit of 96 pM. The method was successfully applied to the recovery analysis of m6A from HeLa cells through spiking experiments and aims to inspire strategies for point-of-care testing (POCT).